2003
DOI: 10.1364/oe.11.002183
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity advantage of swept source and Fourier domain optical coherence tomography

Abstract: Abstract:We present theoretical and experimental results which demonstrate the superior sensitivity of swept source (SS) and Fourier domain (FD) optical coherence tomography (OCT) techniques over the conventional time domain (TD) approach. We show that SS-and FD-OCT have equivalent expressions for system signal-to-noise ratio which result in a typical sensitivity advantage of 20-30dB over TD-OCT. Experimental verification is provided using two novel spectral discrimination (SD) OCT systems: a differential fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
956
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,659 publications
(976 citation statements)
references
References 15 publications
6
956
1
13
Order By: Relevance
“…The instrument is a high-speed UHR OCT system using spectral/Fourier domain detection. [34][35][36] Spectral/Fourier domain detection operates by first measuring the interference spectrum between backscattered or backreflected light from the tissue and light from a stationary reference arm. The magnitude and echo time delay of the light signal from the tissue is measured by taking the Fourier transform of this interference spectrum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument is a high-speed UHR OCT system using spectral/Fourier domain detection. [34][35][36] Spectral/Fourier domain detection operates by first measuring the interference spectrum between backscattered or backreflected light from the tissue and light from a stationary reference arm. The magnitude and echo time delay of the light signal from the tissue is measured by taking the Fourier transform of this interference spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
“…Since we are using a swept source setup, in addition to this analysis the sensitivity advantage of swept source setup must be added. Choma et al [20] have demonstrated that for a Gaussian source an increase is expected in sensitivity compared to δk are bandwidth and linewidth respectively of the light source in k-space. For our SS-OCT system this correspond to an increase of about 22 dB over the corresponding time domain OCT.…”
Section: Experimental Measurements and Discussionmentioning
confidence: 99%
“…The pioneering work in setting the stage for comparison between time domain OCT setups was reported by Rollins and Izatt [5] and Podoleanu [6]. As the interest in Fourier domain and swept source OCT has grown several groups independently proposed method to compare and translate the signal-to-noise results between time domain and Fourier domain systems [18][19][20].In this report we present an SNR analysis of our quadrature interferometric platform as integrated into a time domain system [5] followed by the correction proposed by Choma et al [20] to translate the SNR results for a SS-OCT.…”
Section: Signal To Noise Ratio Analysismentioning
confidence: 99%
“…It is faster than the original optical coherence tomography technique (OCT), i.e. time domain optical coherence tomography (TDOCT), and has a sensitivity advantage [3][4][5]. Achieving ultrahigh resolution in OCT has been difficult to implement due to dispersion mismatch between sample and reference arm [6].…”
Section: Introductionmentioning
confidence: 99%